Cancer Risk for Fingolimod, Natalizumab, and Rituximab in Multiple Sclerosis Patients - Alping, Peter; Askling, Johan; Burman, Joachim; Fink, Katharina; Fogdell‐Hahn, Anna; Gunnarsson, Martin; Hillert, Jan; Langer‐Gould, Annette; Lycke, Jan; Nilsson, Petra; Salzer, Jonatan; Svenningsson, Anders; et al. (Annals of neurology, 2020)
Objective Novel, highly effective disease‐modifying therapies have revolutionized multiple sclerosis (MS) care. However, evidence from large comparative studies on important safety outcomes, such as cancer, is still lacking. Methods In this nationwide register‐based cohort study, we linked data from the Swedish MS register to the Swedish Cancer Register and other national health care and census registers. We included 4,187 first‐ever initiations of rituximab, 1,620 of fingolimod, and 1,670 of natalizumab in 6,136 MS patients matched for age, sex, and location to 37,801 non‐MS general population subjects. Primary outcome was time to first invasive cancer. Results We identified 78 invasive cancers among treated patients: rituximab 33 (incidence rate [IR] per 10,000 person‐years = 34.4, 95% confidence interval [CI] = 23.7–48.3), fingolimod 28 (IR = 44.0, 95% CI = 29.2–63.5), and natalizumab 17 (IR = 26.0, 95% CI = 15.1–41.6). The general population IR was 31.0 (95% CI = 27.8–34.4). Adjusting for baseline characteristics, we found no difference in risk of invasive cancer between rituximab, natalizumab, and the general population but a possibly higher risk with fingolimod compared to the general population (hazard ratio [HR] = 1.53, 95% CI = 0.98–2.38) and rituximab (HR = 1.68, 95% CI = 1.00–2.84). Interpretation In this first large comparative study of 3 highly effective MS disease‐modifying therapies, no increased risk of invasive cancer was seen with rituximab and natalizumab, compared to the general population. However, there was a borderline‐significant increased risk with fingolimod, compared to both the general population and rituximab. It was not possible to attribute this increased risk to any specific type of cancer, and further studies are warranted to validate these findings. ANN NEUROL 2020;87:688–699